A conceptual review of the literature on brand personality - Llanos-Herrera, Gonzalo R. (Estudios de Administración, 2022)
The purpose of this study is to contribute to the knowledge of the systematization of the concept of brand personality by exploring examples of its main research via a review of the literature. We conceptually analyze the brand personality construct and review the extant findings regarding it using the antecedents, consequences and moderators identified by Eisend & Stokburger-Sauer (2013) as our methodological framework.Throughout this work, we provide a series of proposals that pose questions that merit review and exploration. Additionally, we identify some antecedents that point to emerging areas of research, and we posit that these will receive important development in the near future.Recently, the concept of brand personality has become increasingly important via greater theoretical and practical development. This situation constitutes a natural response to the social and technological trends that are taking consumer relationships to a new level. Accordingly, our findings underscore the elements that comprise a favorable context for generating brand personality and highlight its consequences and its impacts.